Developing the information infrastructure based on LADM – the case of Poland. Issue 348 (3rd May 2016) - Góźdź, K. J.; van Oosterom, P. J. M.
Abstract : In this paper, the possibilities of developing the national information infrastructure by applying the Land Administration Domain Model (LADM) are discussed. Confirmation of the legitimacy of using the LADM within the (Spatial) Information Infrastructure (SII) context is illustrated with the case of Poland. Creating the information infrastructure is an immense challenge because its components are usually dispersed among various institutions responsible for their maintenance and dissemination. Co-existing spatial and non-spatial components of the information infrastructure require their proper integration. Moreover, the interdisciplinary nature of the SII results in combining objects from physical and legal world in one computer environment. The process of standardisation is the first step to refine land administration system and to make it more understandable and transparent for involved parties. The LADM, being officially adopted as an international standard ISO 19152, gives a basis for building national profiles and supports creating the European information infrastructure, enabling communication based on common terminology. This paper provides a brief overview of the current land information system in Poland emphasising the main issues in creating the national information infrastructure. Then, the general concept of the country profile for Poland with the adaptation of the LADM is described. With respect to the users' expectations and requirements, the conceptual model is extended to information being outside the scope of LADM. As a final point, several technical aspects of implementing the complemented LADM country profile are explored. The results indicate that effective functioning of the information infrastructure requires proper integration of data, proceeded by analysing the contents of existing data sets, indicating key registers and defining a linkage system between them.